Deciphering nickel-catalyzed electrochemical ammonia synthesis from nitric oxide - Zhao, Siwen (2024)
Electrochemical nitric oxide (NO) reduction to ammonia (NH3) is an attractive nitrogen fixation way; however, the poor mechanistic understanding and unsatisfied NH3 selectivity strongly impede its practical applications. Here, we screened a suite of transition-metal electrocatalysts, in which Ni outperformed others at the top of a volcano-shaped plot. We rationally fabricated five monocrystalline Ni electrocatalysts and observed higher productivities on high-index facets. In particular, Ni(210) demonstrates a unique NH3 selectivity with a yield rate 2-fold higher than those of low-index facets. The energy required for key intermediates switching from hollow-to-bridge sites was established as a descriptor for NH3 production. Electrochemical measurements on Ni nanoparticle ensembles evidenced a high NH3 selectivity of over 85% with a decent production rate, along with a stable running over 50 h. This work guides the rational design of NO reduction electrocatalysts and establishes a paradigm to understand the structure-function correlation in catalysis.